Pengaruh Pupuk NPK dan Jenis Pupuk Organik Terhadap Pertumbuhan dan Produksi Tanaman Kangkung Darat (Ipomoea reptans Poir) - Laia, Fajarman; Zulfida, Ida; Harahap, Rahmaniah (UNIVERSITAS LABUHANBATU, 2023)
Water spinach (Ipomea reptans Poir) is a type of vegetable that is very popular among Indonesians because of its delicious taste. This plant originated in India but then spread to various countries in Asia and Africa (Plucknett and Beemer, 1981). NPK fertilizer in water spinach cultivation is the most widely used compound fertilizer containing the nutrients Nitrogen, Phosphorus and Potassium. Organic fertilizers are fertilizers composed of living matter, such as weathering of plant, animal and human remains. This research will be carried out in the experimental field of the Faculty of Agriculture, Indonesian Community Development University UPMI Medan, on Jl. Waqf, Pasar 12 Marindal II, Patumbak District, Deli Serdang Regency, North Sumatra Province. Altitude 40 m above sea level. Based on the results of field observations, it directly shows the normal growth of land kangkong plants (Ipomoea reptans Poir.). Parameters observed included plant height (cm), number of leaves (strands), sample wet weight (g), overall wet weight (g), root length (cm) and root volume (mm). Single effect NPK fertilizer application at N2 level (1.5 gram/plant (300 kg/ha) has an effect on increasing plant height growth at 3 WAP) based on the 5% DMRT test. The interaction effect of NPK fertilizer and liquid organic fertilizer had no effect on plant height, number of leaves, sample wet weight, overall wet weight, root length and root volume.